Music and religion in the writings of Ian McEwan - Quinn, Iain 1973- (The Boydell Press, 2023)
This book examines Ian McEwan's ability to discern in his writing sentiments that easily resonate with musicians, explores the value of music in exhibiting McEwan's views on the world, and presents his perspective on religion's role within society
Title from publisher's bibliographic system (viewed on 15 Dec 2023)
Keywords: McEwan, Ian / Criticism and interpretation; Music in literature; Religion in literature